2023
DOI: 10.3390/ijms24065525
|View full text |Cite
|
Sign up to set email alerts
|

Acute ACAT1/SOAT1 Blockade Increases MAM Cholesterol and Strengthens ER-Mitochondria Connectivity

Abstract: Cholesterol is a key component of all mammalian cell membranes. Disruptions in cholesterol metabolism have been observed in the context of various diseases, including neurodegenerative disorders such as Alzheimer’s disease (AD). The genetic and pharmacological blockade of acyl-CoA:cholesterol acyltransferase 1/sterol O-acyltransferase 1 (ACAT1/SOAT1), a cholesterol storage enzyme found on the endoplasmic reticulum (ER) and enriched at the mitochondria-associated ER membrane (MAM), has been shown to reduce amyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…Regulation of the enzymatic activity through a differential localization would be a conceivable scenario. It is also possible that the translocation of ACAT into vesicles is associated with the strengthening of ERmitochondria connectivity in response to ACAT inhibition as recently reported [25].…”
Section: Discussionmentioning
confidence: 58%
“…Regulation of the enzymatic activity through a differential localization would be a conceivable scenario. It is also possible that the translocation of ACAT into vesicles is associated with the strengthening of ERmitochondria connectivity in response to ACAT inhibition as recently reported [25].…”
Section: Discussionmentioning
confidence: 58%
“…Nanoparticles were prepared based on the procedure described in [ 48 ]. We previously found that when the high-affinity ACAT inhibitor such as F12511 or K604 are added to cells, the inhibition of the ACAT enzyme by F12511 or K604 remains unaffected by cell washing or the cell homogenization preparation process [ 24 , 48 ]. This finding implicates that once the inhibitor binds to the ACAT enzyme, it stays firmly bound for a few hours before dissociating from the enzyme.…”
Section: Resultsmentioning
confidence: 99%
“…In various cell types in the CNS, the gene expression levels of ACAT1 are much higher than those of ACAT2 (data retrieved from the public domain can be found in [ 20 ]). ACAT1 and ACAT2 are membrane proteins located in the endoplasmic reticulum (ER), and both enzymes are allosterically activated by sterols [ 21 , 22 , 23 , 24 ]. In addition, in microglia isolated from various neurodegenerative diseases and in vulnerable regions of human brains from LOAD, the ACAT1/SOAT1 gene is modestly induced (data retrieved from public domain can be found in [ 20 ]).…”
Section: Introductionmentioning
confidence: 99%
“…With respect to AD, C99 induces the formation of MAM via its ability to bind and “cluster” cholesterol, forming the raft, as described above. In turn, several proteins are recruited to the MAM so as to co-regulate multiple homeostatic pathways, some of which have been described above (e.g., cholesteryl ester synthesis via ACAT1 [ 219 ]). Alterations in the regulation of MAM formation, as occurs in AD, perturbs these pathways.…”
Section: Mam: a Lipid Raft In The Ermentioning
confidence: 99%